The Influence of Pearlescent Pigments Printed on Plastic Packaging on the Print Gloss (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
This study investigates the influence of pearlescent pigments printed on polypropylene (PP) packaging on print gloss, focusing on different viewing angles and background colors. Pearlescent pigments, known for their special luster and interference properties, are increasingly used in the packaging industry to increase visual appeal and differentiate products on the shelf. Five different pearlescent pigments (gold, polar white, green, blue and lilac) with the same particle size were used in the study. All pigments consist of thin platelets of the natural material mica, which are coated with a wafer-thin layer of metal oxide. The pigments were overprinted on black background color on printing material (Yupo) using the offset printing process. The print gloss was measured at three different angles (20°, 60°, 85°) using a multi-angle glossmeter, and the pigments were also examined using a scanning electron microscope (SEM). The results show that the background color significantly affects the final appearance of pearlescent pigments, with gloss being higher when printed on a black background than on a white background.